Antifibrotic effect of AD-1 on lipopolysaccharide-mediated fibroblast injury in L929 cells and bleomycin-induced pulmonary fibrosis in mice. Issue 14 (23rd June 2022) - Li, Tao; Chen, Yu; Li, Yuan; Chen, Gang; Zhao, Yuqing; Su, Guangyue
Abstract : AD-1 has an anti-PF effect and its anti-PF mechanism may be related to its anti-inflammatory and antioxidant effects, and to its capacity to inhibit apoptosis and regulate the TGF-β1/TIMP-1/α-SMA signaling pathway. Abstract : 20( R )-25-methoxyl-dammarane-3β, 12β, 20-triol (25-OCH3 –PPD, AD-1) is a dammarane ginsenoside that is isolated from Panax notoginseng . The present study aimed to explore its anti-pulmonary fibrosis (PF) effect in vitro and in vivo . L929 cells were treated with 10 μg mL −1 lipopolysaccharide (LPS) to establish a PF model in vitro and mice were administered with 3.5 mg kg −1 bleomycin (BLM) by endotracheal intubation to establish a PF model in vivo for investigating the anti-PF effect and its potential mechanism. The results demonstrated that AD-1 reduced the injury, extracellular matrix (ECM) buildup and α-smooth muscle actin (α-SMA) protein expression levels of L929 induced by LPS. Oral administration of AD-1 downregulated the expression of interleukins (such as IL-1β, IL-6 and IL-18), increased the expression of superoxide dismutase (SOD) and glutathione (GSH), reduced the lung coefficient and the content of hydroxyproline (HYP), and mediated the Bax/Bcl-2 protein ratio and P-p53, β-catenin and SIRT3 expression in the lung tissue of mice. Furthermore, AD-1 inhibited the expression levels of TGF-β1, TIMP-1 and α-SMA and reduced inflammatory cell infiltration and collagen deposition in the lung tissue of PF mice. These results indicated that AD-1 could alleviate PF both in vitro and in vivo, and the underlying mechanism may be related to the decrease in ECM deposition and inflammation, the enhancement of antioxidant capacity, and the mediation of lung cell apoptosis and the TGF-β1/TIMP-1/α-SMA signaling pathway, which provide a theoretical basis for the rehabilitation treatment of PF.